Internationalisation of Malaysian universities: a case study of the National University of Malaysia / Norzaini Azman and Yang Farina Abd. Aziz - Azman, Norzaini; Abd. Aziz, Yang Farina (ACRULeT, Faculty of Education & UiTM Press, 2006)
The Malaysian government aspires to be the educational centre for excellence in the Asian region. Strategies for internationalisation are central to the scope the Ministry of Higher Education has taken and the goals it has set for the future. This article examines how Universiti Kebangsaan Malaysia (National University of Malaysia) is responding to the internationalisation phenomenon. This paper begins by outlining the rationale for internationalisation strategies and their potential consequences for Malaysian universities in order to set the context for discussion. Using Universiti Kebangsaan Malaysia (UKM) as a case study, this article examines activities involved in the pursuit of internationalisation. The emphasis is on what has been done and achieved thus far by UKM to reflect its image as “the National University with an international reach”. A discussion of UKM’s experience in internationalisation practices will, it is hoped, shed light on the general current state of internationalisation in the Malaysian Public higher education system.